Strengthening the Foundation of Education and Training in Kenya : Opportunities and Challenges in Primary and General Secondary Education - World Bank (Washington, DC, 2013)
The new Government has instituted immediate policy changes in the education sector to jump-start the system. Under the Free Primary Education (FPE) policy started this year, school fees and levies are abolished at primary level, thereby greatly relieving the household burden of financing primary education. Households immediately responded. Including both public and non-public schools, the primary education gross enrollment rate jumped to over 100 percent, with close to 1 million enrollment increase from the previous year. Enrollment in primary schools has reached 7.2 million this year from 6.3 million in 2002. Quality improvement measures have also taken place at this level, with nationwide provision of funding directly to primary schools through a capitation grant of 1,020 Kenyan Shillings per pupil to finance the purchase of textbooks and other teaching and learning materials, as well as to support other school operation activities. The expansion of school enrollment and the improvement of education quality at primary level will continue during the subsequent years. The development at this level has increased pressure on as well as provided opportunities to the other subsectors. A wider sector reform agenda needs to be put in place immediately. The Kenya National Education Conference held in November 2003 provided an opportunity for the discussions of a sector strategic plan with all the stakeholders. A sector-wide program with wider coverage will be developed based on the sector strategic plan. This sector review has emphasized the primary and secondary subsectors, although the postsecondary levels are covered in the discussions of the system coverage, management, and resource allocation. This is mainly owing to the fact that a labor market study is planned to be conducted jointly by the Bank and the Government. The information from that study will be crucial to the analysis of the external efficiency of the sector, particularly with close linkages with postsecondary level education and training.